Reproduction of Continuous Flow Left Ventricular Assist Device Experimental Data by Means of a Hybrid Cardiovascular Model With Baroreflex Control. Issue 6 (1st October 2013) - Fresiello, Libera; Zieliński, Krzysztof; Jacobs, Steven; Di Molfetta, Arianna; Pałko, Krzysztof Jakub; Bernini, Fabio; Martin, Michael; Claus, Piet; Ferrari, Gianfranco; Trivella, Maria Giovanna; Górczyńska, Krystyna; Darowski, Marek; et al.
Abstract Long‐term mechanical circulatory assistance opened new problems in ventricular assist device—patient interaction, especially in relation to autonomic controls. Modeling studies, based on adequate models, could be a feasible approach of investigation. The aim of this work is the exploitation of a hybrid (hydronumerical) cardiovascular simulator to reproduce and analyze in vivo experimental data acquired during a continuous flow left ventricular assistance. The hybrid cardiovascular simulator embeds three submodels: a computational cardiovascular submodel, a computational baroreflex submodel, and a hydronumerical interface submodel. The last one comprises two impedance transformers playing the role of physical interfaces able to provide a hydraulic connection with specific cardiovascular sites (in this article, the left atrium and the ascending/descending aorta). The impedance transformers are used to connect a continuous flow pump for partial left ventricular support (Synergy Micropump, CircuLite, Inc., Saddlebrooke, NJ, USA) to the hybrid cardiovascular simulator. Data collected from five animals in physiological, pathological, and assisted conditions were reproduced using the hybrid cardiovascular simulator. All parameters useful to characterize and tune the hybrid cardiovascular simulator to a specific hemodynamic condition were extracted from experimental data. Results show that the simulator is able to reproduce animal‐specific hemodynamic status both in physiological and pathological conditions, to reproduce cardiovascular left ventricular assist device (LVAD) interaction and the progressive unloading of the left ventricle for different pump speeds, and to investigate the effects of the LVAD on baroreflex activity. Results in chronic heart failure conditions show that an increment of LVAD speed from 20 000 to 22 000 rpm provokes a decrement of left ventricular flow of 35% (from 2 to 1.3 L/min). Thanks to its flexibility and modular structure, the simulator is a platform potentially useful to test different assist devices, thus providing clinicians additional information about LVAD therapy strategy.